High-voltage lithium cobalt oxide positive electrode material as well as method and application for improving spin state of high-voltage lithium cobalt oxide positive electrode material
High-pressure lithium cobalt oxide positive electrode material is prepared through magnetic field assistance and plasma treatment, which improves its spin state Co4+ content and crystallinity, which solves the problems of phase change and side reactions of the material during charging and discharging, and significantly improves the energy density and cycle life of the battery.
Patent Information
- Application Number
- CN202411665132.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-20
AI Technical Summary
During the charging and discharging process, the existing high-voltage lithium cobalt oxide positive electrode materials have poor reversibility of the body phase H1-3/O1 phase transition and irreversible side reactions between the electrode electrolytes, resulting in unstable material interfaces and affecting the energy density and cycle life of the battery.
At least two methods of magnetic field assist, plasma treatment or high-temperature sintering are used to prepare high-pressure lithium cobalt oxide positive electrode material to increase its spin state Co4+ content, realize the arrangement of an ordered layered structure, and inhibit Co4+ dissolution.
By improving the spin state and crystallinity of the material, enhancing Co-O electron orbit coupling, suppressing the instability of the material interface, significantly improving the energy density and cycle life of the battery.
Smart Images

Figure CN119503896A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery preparation, and in particular relates to a high-voltage lithium cobalt oxide positive electrode material and a method and use for improving the spin state thereof. Background Art
[0002] In order to cope with the excessive global carbon emissions and promote the transformation of green energy structure and form, it is imperative to develop renewable clean energy. As a green energy storage product, lithium-ion batteries have many advantages, including high energy density, high power density, long cycle life, no memory effect and long service life. In recent years, large-scale applications have appeared in small and medium-sized portable mobile devices such as notebooks, smart phones, digital cameras, and camcorders. Lithium cobalt oxide (LiCoO2, hereinafter referred to as LCO) with a layered structure is the main component of the positive electrode of lithium-ion batteries. Compared with lithium nickel oxide, lithium iron phosphate and other structures, lithium cobalt oxide has a higher theoretical density and the largest volume specific energy. With the in-depth research and development of LCO materials, the charging voltage of LCO has gradually increased from the initial 4.2V to 4.45V, or even higher voltage levels, and the specific capacity can reach 185mAh g -1 In order to meet the requirements of safety, environmental protection and long-cycle application, efforts should be made to optimize the performance of the new generation of lithium-ion batteries so that they have fast charging properties and higher energy density, thereby demonstrating better performance in actual use.
[0003] At present, most of the consumer batteries that have been developed and utilized are 4.2V lithium cobalt oxide / graphite systems. However, with the national energy layout and expansion, its energy density can no longer meet the actual production needs. Increasing the charging cut-off voltage of lithium cobalt oxide (charging to 4.6V) is an effective way to achieve higher energy density. However, there are some difficulties in developing high-voltage LCO, which limits its application. When charged to above 4.55V, a large number of lithium ions in LCO are released, and it transforms from an electrochemically active hexagonal system to an electrochemically inactive monoclinic system. The occurrence of irreversible phase change is accompanied by more irreversible slip of the Co-O layer; compared with the bulk phase, the surface structure is also severely damaged, and the highly oxidizing Co near the surface 4+ / O n- It will trigger irreversible harmful side reactions between the surface and the electrolyte, resulting in O loss, Co dissolution and interfacial solvent decomposition. At the same time, the surface will undergo structural degradation that is completely opposite to the LCO synthesis process, from LiCoO2 to CoO, which will cause a sharp increase in surface resistance. This irreversible structural degradation process is always accompanied by continuous O loss and continuous failure in the LCO surface area.
[0004] The capacity of high-voltage lithium cobalt oxide positive electrode materials is closely related to the evolution of their crystal structure and the stability of the positive electrode-electrolyte interface (CEI). Therefore, it is crucial to stabilize the bulk structure of high-voltage lithium cobalt oxide and inhibit side reactions.
[0005] At present, the main methods to improve the lithium cobalt oxide positive electrode are surface coating, element doping, and changing the electrolyte composition, so as to improve the long cycle performance of the battery and reduce the loss of irreversible capacity of the battery. However, these technical means are limited to improving the transfer properties of some active substances and slowing down the rate of battery attenuation. It is difficult to fundamentally solve the problems of poor reversibility of bulk H1-3 / O1 phase transition and irreversible side reactions between electrodes and electrolytes, resulting in a significant reduction in available active substances, and little effect on the actual capacity and coulomb efficiency. At present, there is still a lot of room for improvement in the research and development of high-voltage lithium cobalt oxide positive electrode materials. Therefore, designing and developing a simple and effective synthesis method for high-voltage lithium cobalt oxide is crucial to improving its cycle stability, energy density, and power density.
[0006] It has been reported in the literature that oxygen-containing gas is continuously introduced into the roasting device, and the oxygen-containing gas generates positively charged active oxygen (O + , O 2+ , O 3+ etc.), by applying an electromagnetic field in the calcining device to deflect the movement of the active oxygen, confine and enrich near the powder material, and on this basis, improve the utilization rate of the active oxygen, strengthen the oxidation and synthesize the required material. However, it cannot solve the defects of poor reversibility of bulk H1-3 / O1 phase transition of high-voltage lithium cobalt oxide positive electrode materials during charging and discharging and irreversible side reactions between electrodes and electrolytes, and there is no relevant report on how to solve such problems. Summary of the invention
[0007] In view of the above-mentioned deficiencies in the prior art, the present invention provides a high-voltage lithium cobalt oxide positive electrode material and a method and use for improving its spin state. The present invention adopts at least two methods of magnetic field assistance, plasma treatment or high-temperature sintering to prepare a high-spin state Co 4+ High-voltage lithium cobalt oxide positive electrode materials can realize the orderly layered structure arrangement of high-voltage lithium cobalt oxide positive electrode materials; at the same time, the high-voltage range can inhibit Co 4+ Dissolution can solve the defects of unstable material interface.
[0008] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is:
[0009] A method for improving the spin state of a high-voltage lithium cobalt oxide positive electrode material comprises the following steps:
[0010] (1) preparing lithium cobalt oxide crude material, and then crushing and sieving the raw material;
[0011] (2) Collecting the sieved powder and treating the powder by at least two methods selected from the group consisting of magnetic field assistance, plasma treatment, and calcination to obtain a high-voltage lithium cobalt oxide positive electrode material with an elevated spin state.
[0012] Furthermore, in step (1), lithium cobalt oxide is prepared by a sintering method or a hydrothermal synthesis method; and a magnetic field with a strength of 0.2 to 2.5 T is applied during the preparation process.
[0013] Furthermore, the processing process of step (2) is: collecting the sieved powder and placing it in a magnetic field environment for sintering to obtain a high-pressure lithium cobalt oxide positive electrode material with an elevated spin state.
[0014] Furthermore, the processing process of step (2) is: collecting the sieved powder and placing it in a magnetic field and plasma environment for sintering to obtain a high-pressure lithium cobalt oxide positive electrode material with an elevated spin state.
[0015] Furthermore, the processing process of step (2) is: collecting the sieved powder and placing it in a plasma environment for sintering to obtain a high-pressure lithium cobalt oxide positive electrode material with an elevated spin state.
[0016] Furthermore, the treatment process of step (2) is: collecting the sieved powder and placing it in a magnetic field and plasma environment for treatment to obtain a high-voltage lithium cobalt oxide positive electrode material with an increased spin state.
[0017] Furthermore, the magnetic field strength applied in step (2) is 0.2 to 2.5 T.
[0018] Furthermore, the magnetic field strength applied in step (1) is 0.4 to 1 T; the magnetic field strength applied in step (2) is 0.4 to 1 T.
[0019] Furthermore, when preparing lithium cobaltate in step (1), the molar ratio of the cobalt source to the lithium source is 9:8 to 9:2, calculated on the molar ratio of cobalt to lithium.
[0020] Furthermore, the molar ratio of the cobalt source to the lithium source is 9:4 to 3:1.
[0021] Furthermore, when preparing lithium cobalt oxide in step (1), the cobalt source used is cobalt tetroxide, cobalt oxide, cobalt hydroxide, cobalt sulfate or cobalt oxalate; and the lithium source is lithium carbonate, lithium hydroxide or lithium sulfate.
[0022] Furthermore, after the pulverization in step (1), the powder is sieved to collect powder with a particle size of less than 100 μm for subsequent secondary sintering.
[0023] Furthermore, the sintering temperature in step (1) is 750-950°C.
[0024] Furthermore, the sintering time in step (1) is 14 to 20 hours.
[0025] Furthermore, the sintering temperature in step (2) is 750-950°C.
[0026] Furthermore, the sintering time in step (2) is 14 to 20 hours.
[0027] Furthermore, in step (2), the pressure of the plasma treatment is 3-10 Pa, the temperature during the treatment is 80-950° C., and the working gas is H2 / N2.
[0028] Furthermore, in step (2), the pressure of the plasma treatment is 3-5 Pa, the temperature during the treatment is 100-300° C., and the working gas is H2 / N2.
[0029] Furthermore, in step (2), the pressure of the plasma treatment is 5 Pa, the temperature during the treatment is 120-180° C., and the working gas is H2 / N2.
[0030] A high-voltage lithium cobalt oxide positive electrode material with a high spin state is prepared by the above method.
[0031] The use of the above-mentioned high-voltage lithium cobalt oxide positive electrode material in the preparation of energy storage materials.
[0032] A lithium-ion battery uses the high-voltage lithium cobalt oxide as a positive electrode material.
[0033] Beneficial effects of the present invention:
[0034] 1. The present invention prepares high spin state Co by combining magnetic field assistance, plasma method and sintering. 4+ High-spin Co 4+ The high-voltage lithium cobalt oxide cathode material can enhance the Co-O electron orbital coupling by changing the material electronic state density, further changing the local coordination structure of the CoO6 octahedron, especially in the high cut-off voltage environment. 4+ The coverage of lattice oxygen energy band can anchor the lattice oxygen sites; the volume expansion of lithium cobalt oxide can be suppressed by magnetostrictive effect, and the ordered layered structure of high-voltage lithium cobalt oxide positive electrode can be arranged; at the same time, the high-voltage range can suppress Co 4+ Dissolution can solve the defects of unstable material interface.
[0035] 2. When preparing high-voltage lithium cobalt oxide positive electrode materials, the present invention can improve the crystallinity of the materials, increase the specific surface area, reduce the agglomeration of the materials during growth, and reduce the temperature of the reaction system through plasma treatment. In addition, the introduction of plasma can change the surface properties of high-voltage lithium cobalt oxide, increase the formation energy of oxygen vacancies, and form stable chemical bonds on the surface of the materials to enhance the binding force with the materials, thereby improving the performance and life of the positive electrode materials.
[0036] 3. When preparing high-voltage lithium cobalt oxide positive electrode materials, the present invention adopts a two-step calcination method for processing. After the first sintering, the lattice structure of the material is not completely stable, and defects and impurities may exist. In addition, there is also the problem of uneven distribution of Li and Co ions in the material prepared by the first sintering, and there is a phenomenon of mutual aggregation between the material particles, which is easy to have a negative impact on the battery performance. Therefore, in order to eliminate these defects and impurities, the positive electrode material needs to be ground and sieved, and then the first sintering product with a suitable particle size is selected for secondary sintering, so that the material is recrystallized inside, the lattice is more stable, the defects and impurities are repaired and removed, and the battery performance and stability are improved. At the same time, the secondary sintering can also improve the particle size and distribution of the positive electrode material, increase its charge / discharge rate and cycle life, thereby further improving the battery performance.
[0037] 4. The cut-off voltage of the high-voltage lithium cobalt oxide positive electrode material prepared by the present invention is increased to 4.6V. Compared with the charging voltage of 4.2V of conventional (commercial) lithium cobalt oxide, its charging voltage has been greatly improved, which fully develops the potential of lithium cobalt oxide materials and can greatly improve the energy density of batteries. At the same time, the high-spin state Co in the high-voltage lithium cobalt oxide positive electrode material 4+ The content is higher than that of conventional lithium cobalt oxide, and the high-spin state of Co 4+ Can inhibit Co 4+ dissolution, further improving battery performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The first cycle charge and discharge curve of a battery assembled with the high-voltage lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention;
[0039] Figure 2 A long cycle curve of 300 cycles of charge and discharge of a battery assembled with the high-voltage lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention;
[0040] Figure 3 A graph showing a battery assembled with a high-voltage lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention at different discharge rates;
[0041] Figure 4 The high-voltage lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention has a Co content in the electrolyte after 10 cycles. 4+ Concentration detection;
[0042] Figure 5 Electron microscope images of the electrode / electrolyte interface layer of the high-voltage lithium cobalt oxide positive electrode materials prepared in Example 1 and Comparative Example 3 of the present invention after 10 cycles;
[0043] Figure 6 It is a schematic diagram of the device of the present invention. DETAILED DESCRIPTION
[0044] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0045] Example 1
[0046] A magnetic field assisted sintering method is used to prepare a high-spin state high-voltage lithium cobalt oxide positive electrode material. The specific process is as follows:
[0047] S1. Preparation of lithium cobalt oxide material: 135g of cobalt trioxide and 26.8g of lithium carbonate (cobalt / lithium molar ratio 9:3.5) were mixed evenly, compacted, and loaded into a crucible. The electromagnetic field was turned on with a magnetic field strength of 1T. The mixture was sintered in a muffle furnace at 850°C in an oxygen atmosphere for 16 hours. After sintering, the mixture was cooled, crushed and sieved, and powders with a particle size of less than 100μm were collected.
[0048] S2. After the collected powders are mixed and compacted, they are secondary sintered in an electromagnetic-assisted (1T) muffle furnace at 850° C. in an oxygen atmosphere for 16 hours to obtain a micron-sized high-pressure lithium cobalt oxide positive electrode material.
[0049] Example 2
[0050] A magnetic field assisted sintering method is used to prepare a high-spin state high-voltage lithium cobalt oxide positive electrode material. The specific process is as follows:
[0051] S1. Preparation of lithium cobalt oxide material: 135g of cobalt trioxide and 24.8g of lithium carbonate (cobalt / lithium molar ratio 9:4) were mixed evenly, compacted, and loaded into a crucible. The electromagnetic field was turned on with a magnetic field strength of 0.2T. The mixture was sintered in a muffle furnace at 850°C in an oxygen atmosphere for 18 hours. After sintering, the mixture was cooled, crushed and sieved, and powders with a particle size of less than 100μm were collected.
[0052] S2. After the collected powders are mixed and compacted, they are secondary sintered in an electromagnetic-assisted (0.2T) muffle furnace at 850°C in an oxygen atmosphere for 16 hours to obtain a micron-sized high-pressure lithium cobalt oxide positive electrode material.
[0053] Example 3
[0054] A method for preparing a high-spin-state high-voltage lithium cobalt oxide positive electrode material by using a magnetic field-assisted and plasma method. The specific process is as follows:
[0055] S1. Preparation of lithium cobalt oxide material: Add 93g of cobalt hydroxide to 40mL of anhydrous ethanol and stir continuously for 30 minutes. At the same time, dissolve 9.3g of lithium hydroxide in 40mL of deionized water and dissolve completely (cobalt / lithium molar ratio 9:3.5). Then, add the LiOH solution dropwise to the cobalt hydroxide ethanol solution under vigorous stirring. Stir the mixture for 2 hours to fully mix the components. Subsequently, the solution was transferred to a 100mL polytetrafluoroethylene-lined autoclave and then heated at 180°C for 24 hours. After cooling to room temperature, the precipitate was centrifuged and washed with ultrapure water and ethanol, and then crushed and sieved after drying at 60°C for 12 hours.
[0056] S2. After the collected powders are mixed and compacted, the lithium cobalt oxide precursor is treated in a H2 / N2 plasma atmosphere with the assistance of an electromagnet (1T) to prepare a micron-sized high-pressure lithium cobalt oxide positive electrode material. The process is controlled at a pressure of 8 Pa and a temperature of 120° C. for 2 hours.
[0057] Example 4
[0058] A plasma calcination method is used to prepare a high-spin state high-voltage lithium cobalt oxide positive electrode material. The specific process is as follows:
[0059] S1. Preparation of lithium cobalt oxide material: Add 155g of cobalt sulfate to 40mL of anhydrous ethanol and stir continuously for 30 minutes. At the same time, dissolve 42.8g of lithium sulfate in 40mL of deionized water and dissolve completely (cobalt / lithium molar ratio 9:3.5). Then, add the Li2SO4 solution dropwise to the cobalt sulfate ethanol solution under vigorous stirring. Stir the mixture for 2 hours to fully mix the components. Subsequently, the solution was transferred to a 100mL polytetrafluoroethylene-lined autoclave and then heated at 180°C for 24 hours. After cooling to room temperature, the precipitate was centrifuged and washed with ultrapure water and ethanol, and then dried at 60°C for 12 hours.
[0060] S2. After mixing and compacting the above collected powders, the cobalt oxide precursor is processed in a H2 / N2 plasma atmosphere to prepare a micron-sized high-pressure cobalt oxide positive electrode material. The process is controlled to be carried out at a pressure of 3 Pa and a temperature of 150°C for 2 hours. Finally, a secondary sintering is performed at 850°C in an oxygen atmosphere for 20 hours to obtain a micron-sized high-pressure cobalt oxide positive electrode material.
[0061] Example 5
[0062] A magnetic field assisted plasma method is used to prepare a high-spin state high-voltage lithium cobalt oxide positive electrode material. The specific process is as follows:
[0063] S1. Preparation of lithium cobalt oxide material: 135g of cobalt trioxide and 26.8g of lithium carbonate (cobalt / lithium molar ratio 9:3.5) were mixed evenly, compacted, and loaded into a crucible. The electromagnetic field was turned on with a magnetic field strength of 2.5T. The mixture was sintered in a muffle furnace at 850°C in an oxygen atmosphere for 14 hours. After sintering, the mixture was cooled, crushed and sieved, and powders with a particle size of less than 100μm were collected.
[0064] S2. After mixing and compacting the above collected powders, the cobalt oxide precursor is processed in a H2 / N2 plasma atmosphere to prepare a micron-sized high-pressure cobalt oxide positive electrode material. The process is controlled to be carried out at a pressure of 5 Pa and a temperature of 150°C for 2 hours. In an electromagnetic-assisted (2.5T) muffle furnace, secondary sintering is performed at 850°C in an oxygen atmosphere for 20 hours to obtain a micron-sized high-pressure cobalt oxide positive electrode material.
[0065] Example 6
[0066] A magnetic field assisted plasma method is used to prepare a high-spin state high-voltage lithium cobalt oxide positive electrode material. The specific process is as follows:
[0067] S1. Preparation of lithium cobalt oxide material: 135g of cobalt trioxide and 26.8g of lithium carbonate (cobalt / lithium molar ratio 9:3.5) were mixed evenly, compacted, and loaded into a crucible. The electromagnetic field was turned on with a magnetic field strength of 1.25T. The mixture was sintered in a muffle furnace at 750°C in an oxygen atmosphere for 16 hours. After sintering, the mixture was cooled, crushed and sieved, and powders with a particle size of less than 100μm were collected.
[0068] S2. After mixing and compacting the above collected powders, the cobalt oxide precursor is processed in a H2 / N2 plasma atmosphere to prepare a micron-sized high-pressure cobalt oxide positive electrode material. The process is controlled to be carried out at a pressure of 10Pa and a temperature of 150°C for 2 hours. In an electromagnetic-assisted (1.2T) muffle furnace, secondary sintering is performed at 750°C in an oxygen atmosphere for 14 hours to obtain a micron-sized high-pressure cobalt oxide positive electrode material.
[0069] Example 7
[0070] A magnetic field assisted sintering method is used to prepare a high-spin state high-voltage lithium cobalt oxide positive electrode material. The specific process is as follows:
[0071] S1. Preparation of lithium cobalt oxide material: 135g of cobalt trioxide and 26.8g of lithium carbonate (cobalt / lithium molar ratio 9:3.5) were mixed evenly, compacted, and loaded into a crucible. The electromagnetic field was turned on with a magnetic field strength of 1T. The mixture was sintered in a muffle furnace at 950°C in an oxygen atmosphere for 16 hours. After sintering, the mixture was cooled, crushed and sieved, and powders with a particle size of less than 100μm were collected.
[0072] S2. After the collected powders are mixed and compacted, they are secondary sintered in an electromagnetically assisted (1T) muffle furnace at 950° C. in an oxygen atmosphere for 20 hours to obtain a micron-sized high-pressure lithium cobalt oxide positive electrode material.
[0073] Example 8
[0074] A magnetic field assisted sintering method is used to prepare a high-spin state high-voltage lithium cobalt oxide positive electrode material. The specific process is as follows:
[0075] S1. Preparation of lithium cobalt oxide material: 135g of cobalt trioxide and 26.8g of lithium carbonate (cobalt / lithium molar ratio 9:3.5) were mixed evenly, compacted, and loaded into a crucible. The electromagnetic field was turned on with a magnetic field strength of 1T. The mixture was sintered in a muffle furnace at 850°C in an oxygen atmosphere for 14 hours. After sintering, the mixture was cooled, crushed and sieved, and powders with a particle size of less than 100μm were collected.
[0076] S2. After the collected powders are mixed and compacted, they are secondary sintered in an electromagnetic-assisted (2.5T) muffle furnace at 850°C in an oxygen atmosphere for 14 hours to obtain a micron-sized high-pressure lithium cobalt oxide positive electrode material.
[0077] Example 9
[0078] A magnetic field assisted sintering method is used to prepare a high-spin state high-voltage lithium cobalt oxide positive electrode material. The specific process is as follows:
[0079] S1. Preparation of lithium cobalt oxide material: 135g of cobalt trioxide and 26.8g of lithium carbonate (cobalt / lithium molar ratio 9:3.5) were mixed evenly, compacted, and loaded into a crucible. The electromagnetic field was turned on with a magnetic field strength of 1T. The mixture was sintered in a muffle furnace at 850°C in an oxygen atmosphere for 18 hours. After sintering, the mixture was cooled, crushed and sieved, and powders with a particle size of less than 100μm were collected.
[0080] S2. After the collected powders are mixed and compacted, they are secondary sintered in an electromagnetic-assisted (1T) muffle furnace at 850° C. in an oxygen atmosphere for 18 hours to obtain a micron-sized high-pressure lithium cobalt oxide positive electrode material.
[0081] Comparative Example 1
[0082] A method for synthesizing a high-voltage lithium cobalt oxide positive electrode material with magnetic field assistance is different from that in Example 1 in that the molar ratio of cobalt oxide to lithium carbonate in the synthesis is different. The specific process is as follows:
[0083] Preparation of lithium cobalt oxide material: 135g of cobalt trioxide and 20.1g of lithium carbonate (cobalt / lithium molar ratio 9:8) were mixed and compacted, then loaded into a crucible, and the electromagnetic field was turned on with a magnetic field strength of 1T. The mixture was sintered in a muffle furnace at 850℃ in an oxygen atmosphere for 16 hours. After sintering, the mixture was cooled and crushed and sieved. After the crushed mixture was compacted, it was sintered again in a muffle furnace at 850℃ in an oxygen atmosphere for 16 hours to obtain a micron-sized high-pressure lithium cobalt oxide positive electrode material.
[0084] Comparative Example 2
[0085] A method for synthesizing a high-voltage lithium cobalt oxide positive electrode material with magnetic field assistance is different from that in Example 1 in that the molar ratio of cobalt oxide to lithium carbonate in the synthesis is different. The specific process is as follows:
[0086] Preparation of lithium cobalt oxide material: 135g of cobalt trioxide and 33.5g of lithium carbonate (cobalt / lithium molar ratio 9:2) were mixed and compacted, then loaded into a crucible, and the electromagnetic field was turned on with a magnetic field strength of 1T. The mixture was sintered in a muffle furnace at 850℃ in an oxygen atmosphere for 16 hours. After sintering, the mixture was cooled down and crushed and sieved. After the crushed mixture was compacted, it was sintered again in a muffle furnace at 850℃ in an oxygen atmosphere for 16 hours to obtain a micron-sized high-pressure lithium cobalt oxide positive electrode material.
[0087] Comparative Example 3
[0088] A method for synthesizing a high-voltage lithium cobalt oxide positive electrode material without magnetic field assistance is different from Example 1 in that the synthesis process is carried out without applying a magnetic field. The specific process is as follows:
[0089] Preparation of lithium cobalt oxide material: 135g of cobalt trioxide and 26.8g of lithium carbonate (cobalt / lithium molar ratio 9:3.5) were mixed and compacted, then loaded into a crucible and sintered in a muffle furnace at 850℃ in an oxygen atmosphere for 16 hours. After sintering, the mixture was cooled and crushed and sieved. After the crushed mixture was compacted, it was sintered again in a muffle furnace at 850℃ in an oxygen atmosphere for 16 hours to obtain a micron-sized high-pressure lithium cobalt oxide positive electrode material.
[0090] Comparative Example 4
[0091] A method for synthesizing a high-voltage lithium cobalt oxide positive electrode material with magnetic field assistance is different from Example 1 in that the synthesis process is carried out under a strong magnetic field. The specific process is as follows:
[0092] Preparation of lithium cobalt oxide material: 135g of cobalt trioxide and 26.8g of lithium carbonate (cobalt / lithium molar ratio 9:3.5) were mixed and compacted, then loaded into a crucible, and the electromagnetic field was turned on with a magnetic field strength of 3T. The mixture was sintered in a muffle furnace at 850℃ in an oxygen atmosphere for 16 hours. After sintering, the mixture was cooled down for crushing and sieving. After the crushed mixture was compacted, it was sintered again in an electromagnetically assisted (1T) muffle furnace at 850℃ in an oxygen atmosphere for 16 hours to obtain a micron-sized high-pressure lithium cobalt oxide positive electrode material.
[0093] Comparative Example 5
[0094] A method for synthesizing a high-voltage lithium cobalt oxide positive electrode material with magnetic field assistance is different from that in Example 1 in that the synthesis process temperature is different. The specific process is as follows:
[0095] Preparation of lithium cobalt oxide material: 135g of cobalt trioxide and 26.8g of lithium carbonate (cobalt / lithium molar ratio 9:3.5) were mixed and compacted, then loaded into a crucible, and the electromagnetic field was turned on with a magnetic field strength of 1T. The mixture was sintered in a muffle furnace at 450℃ in an oxygen atmosphere for 16 hours. After sintering, the mixture was cooled down and crushed and sieved. After the crushed mixture was compacted, it was sintered again in an electromagnetically assisted (1T) muffle furnace at 450℃ in an oxygen atmosphere for 16 hours to obtain a micron-sized high-pressure lithium cobalt oxide positive electrode material.
[0096] Comparative Example 6
[0097] A method for synthesizing a high-voltage lithium cobalt oxide positive electrode material with magnetic field assistance is different from that in Example 1 in that the synthesis process temperature is different. The specific process is as follows:
[0098] Preparation of lithium cobalt oxide material: 135g of cobalt trioxide and 26.8g of lithium carbonate (cobalt / lithium molar ratio 9:3.5) were mixed and compacted, then loaded into a crucible, and the electromagnetic field was turned on with a magnetic field strength of 1T. The mixture was sintered in a muffle furnace at 1050℃ in an oxygen atmosphere for 16 hours. After sintering, the mixture was cooled down for crushing and sieving. After the crushed mixture was compacted, it was sintered again in an electromagnetically assisted (1T) muffle furnace at 1050℃ in an oxygen atmosphere for 16 hours to obtain a micron-sized high-pressure lithium cobalt oxide positive electrode material.
[0099] Comparative Example 7
[0100] A method for synthesizing a high-voltage lithium cobalt oxide positive electrode material with magnetic field assistance is different from that in Example 1 in that the sintering atmosphere during the synthesis process is different. The specific process is as follows:
[0101] Preparation of lithium cobalt oxide material: 135g of cobalt trioxide and 26.8g of lithium carbonate (cobalt / lithium molar ratio 9:3.5) were mixed and compacted, then loaded into a crucible, and the electromagnetic field was turned on with a magnetic field strength of 1T. The mixture was sintered in a muffle furnace at 850℃ in an air atmosphere for 16 hours. After sintering, the mixture was cooled down for crushing and sieving. After the crushed mixture was compacted, it was sintered again in an electromagnetically assisted (1T) muffle furnace at 850℃ in an air atmosphere for 16 hours to obtain a micron-sized high-pressure lithium cobalt oxide positive electrode material.
[0102] Comparative Example 8
[0103] A method for synthesizing a high-voltage lithium cobalt oxide positive electrode material with magnetic field assistance is different from that in Example 1 in that the sintering time during the synthesis process is different. The specific process is as follows:
[0104] Preparation of lithium cobalt oxide material: 135g of cobalt trioxide and 26.8g of lithium carbonate (cobalt / lithium molar ratio 9:3.5) were mixed and compacted, then loaded into a crucible, and the electromagnetic field was turned on with a magnetic field strength of 1T. The mixture was sintered in a muffle furnace at 850℃ in an oxygen atmosphere for 12 hours. After sintering, the mixture was cooled down for crushing and sieving. After the crushed mixture was compacted, it was sintered again in an electromagnetically assisted (1T) muffle furnace at 850℃ in an oxygen atmosphere for 12 hours to obtain a micron-sized high-pressure lithium cobalt oxide positive electrode material.
[0105] Comparative Example 9
[0106] A method for synthesizing a high-voltage lithium cobalt oxide positive electrode material with magnetic field assistance is different from that in Example 1 in that the sintering time during the synthesis process is different. The specific process is as follows:
[0107] Preparation of lithium cobalt oxide material: 135g of cobalt trioxide and 26.8g of lithium carbonate (cobalt / lithium molar ratio 9:3.5) were mixed and compacted, then loaded into a crucible, and the electromagnetic field was turned on with a magnetic field strength of 1T. The mixture was sintered in a muffle furnace at 850℃ in an oxygen atmosphere for 20 hours. After sintering, the mixture was cooled down for crushing and sieving. After the crushed mixture was compacted, it was sintered again in an electromagnetically assisted (1T) muffle furnace at 850℃ in an oxygen atmosphere for 20 hours to obtain a micron-sized high-pressure lithium cobalt oxide positive electrode material.
[0108] Comparative Example 10
[0109] A method for synthesizing a high-voltage lithium cobalt oxide positive electrode material is different from that of Example 1 in that the finished product lithium cobalt oxide is directly used to prepare the positive electrode material. The specific process is as follows:
[0110] The finished lithium cobalt oxide was collected and sieved, and then made into a positive electrode material according to the method described in Example 1.
[0111] Comparative Example 11
[0112] A method for synthesizing a high-voltage lithium cobalt oxide positive electrode material is different from that of Example 1 in that only one sintering process is performed during the synthesis. The specific process is as follows:
[0113] Preparation of lithium cobalt oxide material: 135g of cobalt trioxide and 20.1g of lithium carbonate (cobalt / lithium molar ratio 9:3.5) were mixed evenly, compacted, loaded into a crucible, and sintered at 850°C in an oxygen atmosphere in a muffle furnace for 16 hours. After sintering, the mixture was cooled and crushed and sieved to obtain micron-sized high-pressure lithium cobalt oxide positive electrode material.
[0114] Comparative Example 12
[0115] A method for synthesizing a high-voltage lithium cobalt oxide positive electrode material with magnetic field assistance is different from that in Example 1 in that the two sintering temperatures in the synthesis are different. The specific process is as follows:
[0116] Preparation of lithium cobalt oxide material: 135g of cobalt trioxide and 20.1g of lithium carbonate (cobalt / lithium molar ratio 9:3.5) were mixed and compacted, then loaded into a crucible, and the electromagnetic field was turned on with a magnetic field strength of 1T. The mixture was sintered in a muffle furnace at 450℃ in an oxygen atmosphere for 16 hours. After sintering, the mixture was cooled down and crushed and sieved. After the crushed mixture was compacted, it was sintered again in a muffle furnace at 850℃ in an oxygen atmosphere for 16 hours to obtain a micron-sized high-pressure lithium cobalt oxide positive electrode material.
[0117] The performance of the high-voltage lithium cobalt oxide positive electrode materials prepared in the examples of the present invention and the comparative examples and the performance of the batteries assembled therefrom were tested, as follows:
[0118] 1. A battery was assembled using the high-voltage lithium cobalt oxide positive electrode materials prepared in Examples 1 to 9 and Comparative Examples 1 to 9. The positive and negative active materials of the battery were respectively the synthesized high-voltage lithium cobalt oxide and graphite, and the electrolyte was 1 mol / L LiPF6-EC / DEC ester electrolyte.
[0119] Then the electrochemical performance is tested. The results are shown in Table 1. The specific process of the electrochemical performance test is as follows:
[0120] (1) First, the battery is activated with a voltage control range of 3.0 to 4.6 V. The battery is charged to 4.6 V at a constant current of 19 mA / g to obtain the charging capacity. The battery is allowed to stand for 1 min and then discharged to 3.0 V at a constant current of 19 mA / g to obtain the discharge capacity. The discharge specific capacity = discharge capacity / mass of positive electrode active material.
[0121] (2) Then, a cycle test was performed, with constant current charge and discharge at 190 mA / g, and the n-th capacity retention rate was obtained = n-th discharge capacity / first discharge capacity.
[0122] (3) Spin state determination: The high-spin Co content in the synthetic material is determined by a comprehensive physical property measurement system (PPMS).
[0123] (4) Co in electrolyte 4+ Content test: The chemical composition of the electrolyte after five cycles of high-voltage lithium cobalt oxide was determined by inductively coupled plasma (ICP).
[0124] (5) Characterization of the electrode / electrolyte interface layer: The surface morphology and physical state of the high-voltage lithium cobalt oxide electrode / electrolyte interface layer were compared by transmission electron microscopy (TEM).
[0125] Table 1 Electrochemical performance of batteries assembled with different high-voltage lithium cobalt oxide cathode materials
[0126]
[0127] 2. Detect the charge-discharge curve, rate curve, and Co content in the electrolyte of the high-voltage lithium cobalt oxide positive electrode material prepared by Example 1 and Comparative Example 3 of the present invention. 4+ Solubility, transmission electron microscopy photos of the interface layer, the results are shown in Figures 1 to 5 .
[0128] like Figure 1 As shown, the battery assembled with the high-voltage lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention has a first-cycle charge capacity of 257 mAh / g, a first-cycle discharge capacity of 226 mAh / g, a first coulombic efficiency of 88.1%, and an energy density of 247 Wh / kg. Compared with Comparative Example 3 (without applying a magnetic field), magnetic field-assisted synthesis improves the first-cycle charge and discharge capacity of the lithium cobalt oxide battery, improves the first coulombic efficiency, makes full use of the active substances in the positive and negative electrode materials, and obtains a higher energy density.
[0129] like Figure 2 As shown, the long cycle curve of 300 cycles of charge and discharge of the battery assembled with the high-voltage lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention has a capacity retention rate of 85.5%. Compared with Comparative Example 3, the cycle life of the high-voltage lithium cobalt oxide battery is improved, indicating that the chemical stability of the positive electrode material is improved under the action of the magnetic field.
[0130] like Figure 3 As shown, compared with Comparative Example 3, the rate performance of the battery assembled using the high-voltage lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention is improved, and the battery polarization is significantly improved under high current charge and discharge.
[0131] like Figure 4 As shown in the figure, after 10 cycles of the high-voltage lithium cobalt oxide prepared in Example 1 of the present invention, the content of Co in the electrolyte is 4+The concentration of Co is 0.28ppm, which is much lower than 2.64ppm in Comparative Example 3, proving that this technical solution can effectively inhibit the 4+ Dissolution increases the actual capacity of high-voltage lithium cobalt oxide.
[0132] like Figure 5 As shown, compared with Comparative Example 3, the electrode / electrolyte interface layer of the high-voltage lithium cobalt oxide prepared by Example 1 of the present invention is thin and uniform after 10 cycles, indicating that the side reaction between the electrode and the electrolyte is suppressed, solving the defect of unstable material interface.
[0133] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for improving the spin state of a high-voltage lithium cobalt oxide positive electrode material, characterized in that: The following steps are involved: (1) preparing lithium cobalt oxide crude material, and then crushing and sieving the raw material; (2) Collecting the sieved powder, and treating the powder by at least two methods selected from the group consisting of magnetic field assistance, plasma treatment, and calcination, to obtain a high-voltage lithium cobalt oxide positive electrode material with an elevated spin state.
2. The method according to claim 1, characterized in that In the process of preparing lithium cobalt oxide in step (1), a magnetic field with a strength of 0.2 to 2.5 T is also applied.
3. The method according to claim 1 or 2, characterized in that: The magnetic field strength applied in step (2) is 0.2 to 2.5 T.
4. The method according to claim 1, characterized in that: When preparing lithium cobaltate in step (1), the molar ratio of the cobalt source to the lithium source is 9:8 to 9:2, calculated on the molar ratio of cobalt to lithium.
5. The method according to claim 4, characterized in that The cobalt source is cobalt tetroxide, cobalt oxide, cobalt hydroxide, cobalt sulfate or cobalt oxalate; the lithium source is lithium carbonate, lithium hydroxide or lithium sulfate.
6. The method according to claim 1, characterized in that The sintering temperature in step (1) is 750-950°C; the sintering temperature in step (2) is 750-950°C.
7. The method according to claim 1, 2 or 6, characterized in that: The pressure of the plasma treatment in step (2) is 3-10 Pa, the temperature during the treatment is 80-950° C., and the working gas is H2 / N2.
8. A high-spin-state high-voltage lithium cobalt oxide positive electrode material, characterized in that: The method is prepared by any one of claims 1 to 8.
9. Use of the high-voltage lithium cobalt oxide positive electrode material according to claim 8 in the preparation of energy storage materials.
10. A lithium ion battery, characterized in that: The high-voltage lithium cobalt oxide described in claim 9 is used as the positive electrode material.
Citation Information
Patent Citations
Two step synthesis method for producing cathode material of lithium ion battery
CN1540781A
All solid secondary battery and its manufacture
JP2000200621A
Sintered body, oriented electrode containing the sintered body, and battery comprising the oriented electrode
JP2012099405A
LITHIUM COBALT OXIDE MATERIAL AND METHOD OF ITS PREPARATION
RU2011125189A